A VERBAL AND NON-VERBAL SIGNS FOUND IN DESCENDANTS MOVIE POSTER - Ni Wayan Sinta Laras Hati; I Made Yogi Marantika (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
The objective of this study is to determine and analyse the verbal and non-verbal signs within the movie poster of "Descendants." The aim is to extract verbal and non-verbal signs and the use of these indicators in conveying the movie's thematic content. The study employs a movie poster from "Descendants" obtained from Pinterest as its primary data source. The study employs a descriptive qualitative approach, applying the theory of semiotics proposed by Saussure in Chandler (2007), the second theory to analyze the meaning of verbal and non-verbal signs proposed by Barthes (1977). Additionally, Cerrato's theory of color meaning (2012) is employed to supplement this analysis. Data collection process involved several sequential steps, including the selection and retrieval of the movie poster from Pinterest, followed by thorough examination and documentation. The result indicate the presence of a total of 10 signs, with 5 verbal and 5 non-verbal signs. The meanings associated with these signs are discerned through an explored of the accompanied textual and visual elements present on the poster. Notably, both verbal and non-verbal signs predominantly encompass connotative meanings. The utilization of actor portraits as part of the non-verbal signs across the movie posters to attract public attention by capitalized on the visual represented of the film's cast.